Trends and development in perioperative enteral nutrition: a systematic bibliometric analysis - Luo, Chen; Yin, Jianing; Sha, Yuejiao; Gong, Wei; Shen, Ling (Frontiers in Nutrition, 2024)
Background: This research aims to explore the intellectual landscape of studies in perioperative enteral nutrition (PEN) and identify trends and research frontiers in the field.Methods: Scientometric research was conducted through the analysis of bibliographic records from the Web of Science Core Collection Database for the period 2014-2023. Analyses performed using CiteSpace software included cooperation network analysis, reference co-citation analysis, and keywords co-occurrence analysis.The analysis included 3671 valid records in the final dataset. Findings indicate an upward trend in annual publications, with the United States leading in research output and Harvard University as the top publishing institution. The Journal of Parenteral and Enteral Nutrition was identified as the most productive journal. Notable research hotspots include enhanced recovery after surgery, early enteral nutrition, intestinal failure, short bowel syndrome, abdominal surgery. Evidence-based articles have emerged as the predominant literature type. Future research trends are anticipated to focus on gut microbiota and patients with congenital heart disease.Our study provides a comprehensive analysis of the publication volume, contributions by country/region and institutions, journal outlets, and reference and keyword clusters in the field of PEN over the decade. The findings provide valuable insights for researchers, policymakers, and clinicians, helping them comprehend the research landscape, identify gaps, and shape future research directions in this field.